Analisis Pemanfaatan Serbuk Cangkang Telur Terhadap Kuat Tekan Beton Geopolimer: Analysis of Egg Shell Powder Utilization on the Compressive Strength of Geopolymer Concrete - Sinta Devi, Debby; Risa Destania, Henggar; Rizky Cahyadi, Muhammad (Universitas Negeri Surabaya, 2024)
The recent development of rapid infrastructure has led to an increase in the application of concrete as the main construction material. Concrete has several virtues, such as high compressive strength, durability, and fire resistance, although its use can have environmental impacts, especially related to carbon emissions from cement production. Geopolymer concrete is an alternative environmentally friendly material that does not require Portland cement. Geopolymer concrete uses an alkaline liquid to react with silica and aluminum from materials such as fly ash and eggshell powder. Fly ash and eggshells, which are industrial and domestic wastes, can be recycled to replace cement, reducing the environmental impact of concrete construction. This study evaluates the utilization of eggshell powder and fly ash on the compressive strength of geopolymer concrete using variations of 40:60, 50:50 and 60:40. The compressive strength test results show that geopolymer concrete with 0% eggshell powder is 30.77 MPa, while for all variations of test specimens, the use of 40% eggshell powder and 60% fly ash produces the highest compressive strength which is 32.33 MPa. This increase in strength is due to magnesium, iron, and calcium carbonate as compounds found in eggshell powder and Portland cement.